Reconstruction of the evolution of multiple sex chromosomes in Leptidea wood white butterflies - Hovorková, Kristýna (Jihočeská univerzita, 2020)
Having a crucial role in many evolutionary processes, such as sex determination, speciation and adaptation, sex chromosomes tend to be highly conserved. Rapidly evolving sex chromosome systems offer a special opportunity to study the evolution of the sex chromosomes in miraculous resolution. Butterflies of genus Leptidea possess a unique species-specific sex chromosome system with 3-4 W and 3-4 Z chromosomes. Using novel genomic tools established for L. juvernica, namely transcriptome-based microarray for comparative genomic hybridization (array-CGH) and a library of bacterial artificial chromosome (BAC) clones, we assembled the physical maps of Z chromosomes in three cryptic Leptidea species (L. juvernica, L. sinapis, and L. reali) by fluorescence in situ hybridization (FISH) of BAC clones containing orthologs of Bombyx mori genes. In all three species, we identified the 'ancestral' Z chromosome and synteny segments of autosomal origin and reconstructed the step-by-step evolution of multiple sex chromosomes. We propose that the multiple sex chromosome system originated in the common ancestor of Leptidea species by means of multiple chromosomal rearrangements, especially translocations, fusions and fissions, between the sex chromosomes and autosomes. Thus, the turnover of neo-sex chromosomes could not be the main engine driving speciation in this genus. Instead, we propose that subsequent differentiation of the sex chromosome multiples in each species together with enlarged number of Z-linked genes could play a crucial role in accumulation of genetic incompatibilities facilitating subsequent divergence and speciation in Leptidea wood white butterflies.
Reconstruction of the evolution of multiple sex chromosomes in Leptidea wood white butterflies
Reconstruction of the evolution of multiple sex chromosomes in Leptidea wood white butterflies
Keywords: Lepidoptera; Leptidea; neo-sex chromosomes; chromosome rearrangements; Z-linked genes; BAC-FISH mapping; cryptic species; speciation; Lepidoptera; Leptidea; neo-sex chromosomes; chromosome rearrangements; Z-linked genes; BAC-FISH mapping; cryptic species; speciation